MORAL DALAM NOVEL MERAH PUTIH TERGADAI DI PERBATASAN KARYA JEMMY SETIAWAN DAN WINSTON NEIL RONDO - Mutazam Arif; Abdoel Gafar; Sujoko Sujoko (Universitas Batanghari, 2021)
The purpose of the research is to describe the form of moral values or teachings in the novel Red and White Tainted in the Borders. The research methodology used is the descriptive analysis method. The data used is secondary data. The novels used are Red and White In The Borders by Jemmy Setiawan and Winston Neil Rondo. This study's result is a form of moral value in the novel Red, and White Tainted in the Borders By Jemmy Setiawan and Winston Neil Rondo consists of three forms. The three forms of moral values are a form of moral value in human relations with God, a form of moral value in human relations with the nation and country, and moral value in human relations with the ruler. Keywords: Moral values, Representation of Moral values